Factors Influencing Students' Interest in Choosing a Career as an Accountant in Islamic Banking with Motivation as a Moderating: English - Amir, Nadia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
This study aims to determine the factors that influence students' career interests to become accountants in Islamic banking. The variables used are Personality, Job Market Considerations and Knowledge of Islamic Accounting with Motivation as a moderating variable. In this research, quantitative approach are used with questionnere method which were addressed to 96 students who already passed the Islamic accounting courses. The data analysis technique uses multiple linear regression with the SPSS version 26 software. The results of this study indicate that the personality variable has a positive and significant effect on career intention to become an accountant, while the labor market considerations and sharia accounting knowledge variables do not have a significant effect on career interest. The motivational variable is unable to moderate the influence of personality, labor market considerations and sharia accounting knowledge on career interest.